Pendidikan Islam di Seluruh Dunia: Komunitas dan Keberagamannya - Firmansyah, Dinata; Ma'mur, Ilzamudin; Gunawan, Agus (IAI Darussalam, 2025)
Islamic education worldwide demonstrates significant diversity, shaped by various social, cultural, historical, and political factors specific to each country. This research explores how Islamic education is implemented across different regions, including the Middle East, South Asia, Southeast Asia, Europe, and America, and how variations in Islamic traditions and interpretations influence educational systems in each community. Using a qualitative approach with descriptive-analytical techniques, the study integrates literature reviews, interviews with Islamic education practitioners, and field observations at representative Islamic educational institutions. The findings reveal that while Islamic education is rooted in the teachings of the Quran and Hadith, its practices vary greatly depending on local socio-cultural contexts. For instance, in the Middle East, Islamic education is often integrated into national education systems, whereas in Western countries, it emphasizes inclusivity and diversity. In conclusion, despite the differences in practice, Islamic education plays a vital role in shaping individual and community character and addressing global challenges in the era of modernization and globalization.